2014
DOI: 10.1159/000366425
|View full text |Cite
|
Sign up to set email alerts
|

O-MAX Chemotherapy: High Activity in Metastatic Esophagogastric Adenocarcinoma and Possible Relation to Subclinical Hemolysis

Abstract: Objectives: Our objectives were to confirm the activity of O-MAX chemotherapy in adenocarcinoma of the stomach and esophagus, particularly the high rate of complete remission (CR) and the relation of subclinical hemolysis to CR. Patients and Methods: Twenty-five patients with metastatic esophagogastric adenocarcinoma were treated with O-MAX. Two developed cancer-related hemolytic-uremic syndrome (C-HUS); both achieved CR. Subsequent patients were monitored for serum haptoglobin for subclinical hemolysis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Chemotherapy-induced anemia can be caused by cytotoxic inhibition of normal hematopoiesis similar to chemotherapy-induced neutropenia and thrombocytopenia. Chemotherapy agent-related autoimmune hemolysis 31,32 and chemotherapy-induced eryptosis can also cause anemia. 33 Our current GWAS studies have found that chemotherapy-induced anemia is associated with SNP in CHPT1, 6 BSG, 11,12 ANAX7, 14 EPB42, 15,16 and ABCC417 that may be related to increased erythrocyte…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy-induced anemia can be caused by cytotoxic inhibition of normal hematopoiesis similar to chemotherapy-induced neutropenia and thrombocytopenia. Chemotherapy agent-related autoimmune hemolysis 31,32 and chemotherapy-induced eryptosis can also cause anemia. 33 Our current GWAS studies have found that chemotherapy-induced anemia is associated with SNP in CHPT1, 6 BSG, 11,12 ANAX7, 14 EPB42, 15,16 and ABCC417 that may be related to increased erythrocyte…”
Section: Discussionmentioning
confidence: 99%
“…The most aggressive gastric cancer treatment regimen that the patient can tolerate is selected. In our patient in this case report the O-MAX regimen was selected [10]. If the response to the systemic chemotherapy is complete or near complete, a gastrectomy to resect the primary disease site and cytoreduction to remove residual sites of peritoneal metastases may be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…2). In the first 25 consecutive patients (all metastatic) treated with O-MAX for adenocarcinoma of the stomach or esophagus, the objective response rate was 90% with 38% complete remissions [10]. Preliminary evidence suggested subclinical hemolysis in complete responders, implying the presence of antitumor antibodies as identified by Camtrell et al [18].…”
Section: Discussionmentioning
confidence: 99%